Usage of wood biomass in cogeneration - Radosavljević, Milan R.; Šušteršič, Vanja M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The potential of biomass in Serbia is large and includes forestry and wood industry residue, firewood, residues from agriculture, biomass collected for maintenance of roads and infrastructure. The construction of cogeneration plants in woody biomass will increase the share of renewable energy sources, and will thus contribute to meeting the multiple objectives of the energy policy document. It is reasonable to assume that the energy needs of the occasional need to use biomass and low quality, which will inevitably affect the operational parameters of the cogeneration plant. In the absence of recent domestic experience is necessary to objectively and impartially analyze information on the current state of technology and information about the operation of cogeneration plants fired with wood biomass (Ewald, Witt, 2006). When choosing a location it is necessary to find a satisfactory compromise between different requirements such as proximity to sources and the possibility of delivering sufficient quantities of biomass, secured access to vehicles that are not connected to the electricity network is a simple and inexpensive, there is a possibility of water and sewer connection, there is a possibility of delay solid fuels, consumers are not far apart, ie. that the lower costs of heat distribution. Approximate cost of connection to the electricity grid to depend on whether it is a new construction or use of the existing electricity network. Serbia is considered medium-forested land. Of the total area of its territory, 29.1% is in the woods which is 2.252 million ha (Figure 1). From that state-owned is 1,194,000 ha, or 53%, a privately owned 1,058,387 hectares or 47% (Figure 2). The forest cover in Serbia is close to the global one which is 30%, and significantly lower than that of Europe which reaches 46%. In relation to the population, the forested area is ​​0.3 ha per capita (in Russia it is 11.11 ha per capita, 6.93 in Norway, in Finland it is 5.91, 1.38 in BiH and in Croatia it is 1.38 ha per capita). Wood biomass includes small amounts of sulfur ( in the trunk there is only 0.01% , in conifer needles the percent is 0.04 to 0.2% - expressed in percentage by weight of dry fuel). In practice, the combustion of biomassyields very small or negligible amounts of sulfur oxide so that in plants that use only wood biomass as fuel, equipment for the removal of sulfur oxides is not installed as a rule.. In the burning process, sulfur builds gaseous compounds SO2 and SO3 and alkali sulfates. In boilers where gases are cooled quickly,sulfates condense on fly ash particles or on pipe surfaces.The majority of sulfur is found in ash (40 to 90 %).The effectiveness of the retention of sulfur in ash depends on the concentration of alkali metal (especially calcium ) in ash.The effect of sulfur is not so significant for SO2 emissions, as is its role in the corrosion process. The nitrogen content in wood biomass is relatively low. The dry tree trunk and the bark contain 0.1-0.5 % of nitrogen, while its content in conifere needles is slightly higher (1-2%). Nitrogen oxides produced during combustion are nitrogen monoxide (NO) and nitrogen dioxide (NO2), commonly designated as NOx. Approximately 85% of nitrogen oxides formed in the combustion process are thermal NOx (at a temperature of 9,000C). Nitrogen oxides are formedby complex processes depending oncombustion technology and temperature.The formation of nitrogen oxides is mostly affected by fuel properties. According to the Institute of Statistics, the total amount of 2.7 million toe represents 40 % of the total coal production in Serbia. Regarding the wood sources, half of them are firewood with the energy value of 240,000 toe, and the rest is natural waste from trees with an energy value of 550,000 toe, where its 42% is not usable at the market, at least for now.The annual yield of residues produced as a by - product of wood processing is 350,000 m3, or 66,900 toe. What is characteristic for some countries is the shortage or absence of certain energy sources. Numerous wars were waged in the past to compensate for what was lacking, e.g. water and food. Today, the main reason for this is energy. In the future, it will be necessary to substitute non-renewable sources of energy with renewable resources; they were used more in the past and there are enough of them to cover all energy needs. Biomass is sure to become a primary source of energy, tand wars for energy will become history.